Standardization of assay representation in the Ontology for Biomedical Investigations. (9th July 2021) - Vita, Randi; Zheng, Jie; Jackson, Rebecca; Dooley, Damion; Overton, James A; Miller, Mark A; Berrios, Daniel C; Scheuermann, Richard H; He, Yongqun; McGinty, Hande Küçük; Brochhausen, Mathias; Lin, Aisyah Yu; et al.
Abstract: The Ontology for Biomedical Investigations (OBI) underwent a focused review of assay term annotations, logic and hierarchy with a goal to improve and standardize these terms. As a result, inconsistencies in W3C Web Ontology Language (OWL) expressions were identified and corrected, and additionally, standardized design patterns and a formalized template to maintain them were developed. We describe here this informative and productive process to describe the specific benefits and obstacles for OBI and the universal lessons for similar projects.